NORMATIVE GAPS IN EMPLOYMENT RIGHTS PROTECTION WITHIN CIVIL SERVICE CONTRACTS IN DIVORCE DISPUTES: A COMPARATIVE STUDY OF INDONESIA AND HUNGARY - Rizqi Hadi Saputro; Kadek Januarsa Adi Sudharma; Talabos Dávidné Lukács Nikolet (Kanun Jurnal Ilmu Hukum, 2025)
This article analyzes a normative gap in the protection of civil servant contracts during divorce disputes by conducting a comparative study between Indonesia and Hungary. This study is normative legal research with a conceptual, comparative, and legislative approach. This article affirms that the issues surrounding the protection of employment rights in civil servant contracts during divorce disputes reveal normative gaps due to the disharmony between legal regimes, particularly between employment law and family law, as well as the weak integration between judicial decisions and administrative implementation. These conditions result in the absence of a clear and uniform mechanism for the implementation of post-divorce economic rights, leading to variations in practices that culminate in legal uncertainty and potential injustice for the parties involved. Through a comparative legal approach between Indonesia and Hungary, this study finds that the difference in the construction of the relationship between the private and public spheres significantly affects the level of labor rights protection, where Indonesia tends to be interventionist (over-regulation), while Hungary emphasizes a clear separation (under-regulation) with stronger individual rights protection. This research emphasizes the need for a reformulation of legal policies that balance institutional interests and private rights through the principles of proportionality, justice, and strengthening implementation mechanisms, to create a more effective, consistent, and substantively just system of labor rights protection in the context of divorce disputes for Civil Servants (PNS).